The interrelationships of university student characteristics and the Keller ARCS motivation model in a blended digital literacy course - Schartz, Shane (Kansas State University, 2014)
The purpose of this study was to examine student motivation in a blended learning digital literacy course and its relation to student characteristics. The study consisted of 136 student participants enrolled in a blended learning digital literacy course at a Midwestern university. The Keller ARCS Motivation Model was the theoretical framework. The Course Interest Survey was used in the study, which was designed to measure motivation using Keller ARCS categories. Data was collected through the Course Interest Survey to voluntary student participants and through data obtained from the research setting. The study examined the following research questions: Research Question 1: Do statistically significant relationships exist between non-performance student characteristics and the Keller ARCS Course Interest Survey student motivation scores in a blended digital literacy course? Research Question 2: Do statistically significant relationships exist between pre-course performance student characteristics and the Keller ARCS Course Interest Survey scores in a blended digital literacy course? Research Question 3: Do statistically significant relationships exist between post-course performance student characteristics and the Keller ARCS Course Interest Survey student motivation scores in a blended digital literacy course? To examine these relationships, the study utilized MANOVAs to analyze the student characteristics on the four categories of the Keller ARCS Motivation Model. One significant relationship was found for Confidence within Academic Rank (p < .05), between Seniors and Freshmen. Seniors reported a .4799 higher Confidence score, on average, than Freshmen. Other characteristics did not have significant relationships. The mean change in pretest and posttest scores in digital literacy on the ALTSA assessment was 6.64. Recommendations for the research setting included the use of student focus groups to better understand and increase Freshmen confidence and the Freshmen experience, a review of course design and delivery methods, an exploration of variations of blended learning models, an examination of current test-out procedures, and adjustment of the scale used in this study to provide a wider range of motivation responses. Recommendations for future studies included a qualitative study of student performance characteristics, a mixed methods study of different learning models for course delivery, and an exploratory study aimed at expanding student characteristics.
Keywords: higher education; motivation; Keller ARCS; digital literacy; Blended learning; Higher Education (0745); Information Technology (0489); Instructional Design (0447)